ChemInform Abstract: Synthesis and Antimalarial Activity of Novel Bicyclic and Tricyclic Aza‐Peroxides. Issue 28 (June 2016) - Yadav, Lalit; Tiwari, Mohit K.; Kumar Shyamlal, Bharti Rajesh; Mathur, Manas; Swami, Ajit K.; Puri, Sunil K.; Naikade, Niraj K.; Chaudhary, Sandeep
Abstract: The title peroxides are prepared using a 1 O2 ‐mediated photo‐oxygenation method as a key step.